Revised Estimation of the External Characteristics of the Power Transformer - Andriušienė, L.; Kairys, A.; Kostrauskas, P. (Elektronika ir Elektrotechnika, 2003)
There are proved that the angle between the primary and secondary windings depends on the relation of short circuit voltage, of thecomponents of short circuit voltage, load factor and power load factor. The maximum value of the angle between the primary andsecondary voltages is achieved when the load has an active character ( 0) 2 ϕ < . The minimum value is achieved when load power factoris about zero. The revised formula of the calculation of the power transformer external characteristic is presented. This formula exactestimates the dependence of the angle between the primary and secondary windings on the short circuit voltage, the relation between theshort circuit voltage components, power factor and load factor. Theoretical conclusions have been compared with experimental results:the discrepancy of the results of the measured and calculated external characteristic of the power transformer is less than 3%, when loadfactor interval is equal (0;3). If load factor is equal 3 the discrepancy of the previous method amounts 30 %. Ill. 3, bibl.5 ( in Lithuanian;summaries in Lithuanian, English, Russian).